Gaya Berkomunikasi Dan Adaptasi Budaya Mahasiswa Batak di Yogyakarta - Oktolina Simatupang; Lusiana Andriani Lubis; Haris Wijaya (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
This research aims to understand communication style and cultural adaptation of Bataknese students from North Sumatera studying at Institut Seni Indonesia Yogyakarta using theories of intercultural communication, communication style and adaptation. This research employs qualitative descriptive method. Data were collected through in-depth interview and observation among ten Bataknese students from North Sumatera studying at Institut Seni Indonesia Yogyakarta. The informants are students who went to primary level to high school in North Sumatera province. Data were analyzed by data processing, categorization and data interpretation. The result shows that most of informants speak directly and explicitly. It means that their communication style tends to be low-context communication. They also experienced culture shock in process of cultural adaptation. Overall, informants are able to adapt well in Yogyakarta’s environment. Their openness and willingness to adapt with a new culture help them to be comfort in new environment.